Strain-Induced Modulation of Spin Configuration in LaCoO3 - Wang, Linxia; Liu, Jieyu; Wu, Minghui; Wu, Hanming; Li, Kaixiang; Shao, Yuankai; Li, Zhenguo; Wang, Weichao (Frontiers in Materials, 2020)
For oxides with octahedron ligand field, such as perovskite, spinel, and mullite, unit occupancy of eg orbital plays a key role to govern the catalytic performance of oxygen redox in the application of renewable energy storage and conversion. The magnetic configurations greatly influence the eg occupancy of these oxides. In this work, taking the perovskite LaCoO3 as an example, we use density functional theory (DFT) calculations to achieve an intermediate spin configuration corresponding to unit-like eg occupancy via strain schemes. It is found that the introduction of strain by changing lattice constants effectively tailors electronic configurations. The low spin (t_2g^6 e_g^0), intermediate spin (t_2g^5 e_g^1), and high spin (t_2g^4 e_g^2) configurations are obtained with the strain γ < 1.0%, 1.0% ≤ γ < 4.0%, and γ ≥ 4.0%, respectively. To obtain the eg unit occupancy practically, Ba with a larger ionic radius relative to La is inserted into A site to replace La elements, introducing tensile strain to the pristine LaCoO3. The Ba substitution of La leads to the desirable spin configuration with the unit-like eg occupancy. These findings provide a scenario on how to precisely control the unit occupancy of eg via defect induced strain.